227k views
4 votes
2) Simplify: 4/3+3/5+-3/5+-11/3​

User Dops
by
5.5k points

1 Answer

1 vote

Answer:


(4)/(3)+(3)/(5)+-(3)/(5)+-(11)/(3)


=(4)/(3)-(11)/(3)


(a)/(c)\pm (b)/(c)=(a\pm \:b)/(c)


=(4-11)/(3)


\:4-11=-7


=(-7)/(3)


\:fraction\:rule}:\quad (-a)/(b)=-(a)/(b)


(-a)/(b)=-(a)/(b)


(-7)/(3)
=-(7)/(3)

---------------------


\boxed{\boxed{\underline{\textsf{\textbf{hope it helps}}}}}


\boxed{\boxed{\underline{\textsf{\textbf{have a great day!}}}}}

User Greg Mathews
by
4.6k points